Os direitos constitucionais trabalhistas e o princípio do não retrocesso social frente à crise do Covid-19 - Costa, Demian Diniz da (Universidade do Vale do Rio dos Sinos, 2021)
Based on the understanding of social labor rights as fundamental rights, this dissertation analyzes the effects and guarantees arising therefrom, seeking the realization of labor rights. We also approach the legal content of the principle of prohibition of social retrogression as a guarantee of the protection of social rights, carrying out jurisprudential research that demonstrates the link of the Labor Court to the principle of prohibition of social retrogression, having as its scope the defense of social labor rights. The dissertation presents the analysis of the principle of non-regression and its impact on the protection and enforcement of social labor rights provided for in the Federal Constitution. The labor reforms carried out in recent years have brought a weakening and restriction of Constitutional Labor Rights due to the Neo-Liberal Agenda of Governments after the 2016 impeachment. justification of necessary measures to fight the unemployed caused by the Covid-19 epidemic.
Keywords: Direitos sociais trabalhistas; Constituição; Direitos fundamentais; Princípio do não-retrocesso social; Covid-19; Social labor rights; Constitution; Fundamental rights; Principle of social non-retrogression; ACCNPQ::Ciências Sociais Aplicadas::Direito